Islamic Religious Counselor Communication Strategy in the Guidance of Converts in Patambia Pinrang - Samsina, Samsina (Al-Iftah: Journal of Islamic studies and society, 2021)
This thesis discusses the communication strategies of Islamic extension agents in fostering converts in Patambia, Pinrang Regency. This research used descriptive qualitative research. The results of this study indicated: (1) The existence of converts in Patambia, Betteng Village, Lembang District, Pinrang Regency, with the large number of converts in Patambia, Betteng Village, Lembang District, shows something positive, namely an indication that the desire of people to convert to Islam is quite large, reaching 128 people. details of 74 male and 54 female. (2) The program for converting converts in Patambia, Betteng Subdistrict, Lembang District, Pinrang Regency, namely: Islamic aqidah development, worship guidance and guidance for reading and writing the Qur'an.